Labor market institutions and the business cycle Unemployment rigidities vs. real wage rigidities - Mirko Abbritti; Sebastian Weber (European Central Bank (ECB), 2010)
This paper investigates the importance of labor market institutions for inflation and unemployment dynamics. Using the New Keynesian framework we argue that labor market institutions should be divided into those institutions that cause Unemployment Rigidities (UR) and those that cause Real Wage Rigidities (RWR). The two types of institutions have opposite effects and their interaction is crucial for the dynamics of inflation and unemployment. We estimate a panel VAR with deterministically varying coefficients and find that there is a profound difference in the responses of unemployment and inflation to shocks under different constellations of the labor market.
Keywords: E32; E24; E52; 330; business cycle; Labor Market Search; monetary policy; Real Wage Rigidity; Unemployment; Reallohn; Lohnrigidität; Arbeitsuche; Neoklassische Synthese; Konjunktur; Geldpolitik; VAR-Modell